MYC Promotes LDHA Expression through MicroRNA-122-5p to Potentiate Glycolysis in Hepatocellular Carcinoma - Xiaofei Wang; Penghua Zhang; Ke Deng (Analytical Cellular Pathology)
MYC is a notorious oncogene in a vast network of malignancies, whereas liver-specific microRNA- (miR-) 122-5p is downregulated in hepatocellular cancer (HCC). Here, we studied the possible correlation between these two and their involvement in glycolysis in HCC. MYC was overexpressed in HCC tissues and cells compared to normal liver tissues and normal hepatocytes NHC, which predicted a poor survival of HCC sufferers. Functional assays demonstrated that silencing of MYC inhibited the glycolysis in HCC cells, as evidenced by significantly weaker glucose consumption, lactate production, adenosine triphosphate (ATP) levels, and downregulated HK1 and HK2 protein expression. Moreover, MYC bound to the miR-122-5p promoter and repressed the miR-122-5p expression. Rescue experiments showed that miR-122-5p inhibitor rescued the diminished glycolysis after MYC silencing. In addition, lactate dehydrogenase (LDHA) was identified as a downstream target of miR-122-5p. The overexpression of LDHA mitigated the effects of si-MYC and miR-122-5p mimic on glycolysis of HCC cells, respectively. In conclusion, the MYC/miR-122-5p/LDHA axis modulates glycolysis in HCC cells and possibly affects HCC progression.